The Influence of Prosedural Justice and Organizational Climate on Organizational Citizenship Behavior (OCB) With Employee Engagement as a Mediator - Ekawati, Erna; Tjahjono, Heru Kurnianto; ., Fauziyah (Account and Financial Management Journal, 2019)
This study aims at analyzing the influence of Procedural Justice, and Organizational Climate on Organizational Citizenship Behavior (OCB) by mediating Employee Engagement. Survey methods with questionnaires were used as data collection techniques. Structural Equation Modeling was used as the data analysis technique. The results showed that organizational climate and employee engagement have a positive and significant effect on OCB; procedural justice and organizational climate have a positive and significant effect on employee engagement, while procedural justice has no significant influence on organizational citizenship behavior, which means rejecting the hypothesis in this study. Organizational climate is the dominant variable in influencing organizational citizenship behavior, therefor special attention and improvement must be made by management.